Thyroid function and serum electrolytes: does an association really exist? (Swiss Medical Weekly, 2012)
BACKGROUND: Thyroid hormone is a central regulator of body functions. Disorders of thyroid function are considered to be a cause of electrolyte disorders. Only few data on the association between thyroid function and electrolyte disorders exists. METHODS: In the present retrospective analysis data from all patients admitted to the Department of Emergency Medicine of a university hospital who had measurements of thyroid function (TSH, fT3, fT4) and electrolytes were included. RESULTS: 9,012 patients with measurement of TSH and electrolytes were available. 86% of patients had normal, 4% suppressed and 10% elevated TSH. Serum sodium was significantly lower in patients with high TSH levels (p